Two Domains to Five: Advancing Veterinary Duty of Care to Fulfil Public Expectations of Animal Welfare Expertise - Littlewood KE; Beausoleil NJ (MDPI (Basel, Switzerland), 2021)
Veterinarians are animal health experts. More recently, they have been conferred a leading role as experts in animal welfare. This expectation of veterinarians as welfare experts appears to stem from their training in veterinary medicine as well as professional contributions to welfare-relevant policy and law. Veterinarians are ideally situated to act as animal welfare experts by virtue of their core work with animals and potential influence over owners, their roles in policy development, compliance, and monitoring, and as educators of future veterinarians. However, since its inception as a discipline over 70 years ago, animal welfare science has moved beyond a two-dimensional focus on nutrition and health (biological functioning) towards an understanding that the mental experiences of animals are the focus of welfare consideration. The Five Domains Model is a structured and systematic framework for more holistically considering conditions that contribute to the animal's internal state and its perception of its external situation, and the resultant mental experiences. The Model can be used to better align veterinary animal welfare expertise with contemporary understanding of animal welfare science and improve welfare literacy within the veterinary profession. Improved understanding of animal welfare science is likely to lead to increased confidence, competence, and empowerment to act as experts in their daily lives.
Keywords: Five Domains Model; animal welfare; animal welfare science; continued professional development; quality of life; veterinarian; veterinary education; welfare enhancement